A reconceptualisation of music performance anxiety - Van Schoor, Nina (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2020)
Music Performance Anxiety (MPA) refers to the potentially debilitating anxiety experienced before and/or during the public performance of music, despite adequate preparation. MPA is generally treated by means of drug therapy, cognitive behavioural therapy, psychoanalysis or various relaxation techniques. This research aims to present a different approach to dealing with MPA, based on a reconceptualisation of the concept. As a result, it attempts to unpack all three concepts inherent in the term from both a psychological and philosophical viewpoint. The study used autoethnography as a methodology, as I wished to explore my own lived experience of MPA and anxiety in general, in conjunction with that of my two participants, two other student Western Art music performers, and how our methods for confronting MPA within the performance context itself suggests a more complex understanding of performance and MPA than is reflected in the current literature. Thus the data was collected from two first-person interviews as well as a self-reflective written account. The results of the analysis were that existential anxiety is potentially a contributing factor to MPA, and that performance itself can potentially provide the very means for overcoming not only MPA, but all forms of anxiety, due to the cathartic quality of music as well as performance, especially when the liminal or interstructural, nature of performing and its ritualistic function is explored. This exploration reveals the world and self-disclosing nature of agency and Play, or the potential within experiences to resolve conflicts and reveal otherness. This requires a degree of existential courage, or an affirmative response to the unknown, which is more relational than the definition suggests. In conclusion, this study reconceptualises MPA as a potentially potent existential experience, and that the anxiety in response to it is considered as a reaction to the catharsis inherent in being an agent, rather than merely as an obstacle to be controlled.
Keywords: Performance anxiety; Music -- Performance -- Psychological aspects; Anxiety